Utilization of State Property in The Development of Sports Businesses of The Public Service Agency for Fund Management and Sports Businesses of The Ministry of Youth and Sports - Fuad Akhdlori; Arifiani Widjayanti; R. Luki Karunia (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to analyze the utilization of State-Owned Movable Goods (BMN) in sports business development at BLU LPDUK and formulate an assessment framework for this utilization based on Institutional KPIs. Employing a qualitative approach, the study reveals that BMN utilization at LPDUK involves cooperation with three business units—SP2OI, ADMI, and ABI—but these activities were discontinued due to budgetary constraints and discrepancies in income generation. Despite proper implementation of safeguarding and maintenance procedures for BMN, including recording and inventorying through the SAKTI system, deficiencies exist in sanction clauses within operational cooperation agreements, hindering effective enforcement when partners fail to fulfill obligations.